(Invited) A Nonvolatile SRAM Based on Ferroelectric HfO2 Capacitor for IoT Power Management. (9th April 2018) - Kobayashi, Masaharu; Ueyama, Nozomu; Hiramoto, Toshiro
Abstract : A nonvolatile SRAM has been designed and fabricated by integrating with ferroelectric HfO2 capacitors, and its store/recall operation before/after power-off have been experimentally demonstrated. Excellent ferroelectricity and memory characteristics have been obtained in sub-10nm-thick ferroelectric HfO2 capacitor. The NVSRAM with ferroelectric HfO2 capacitor can be a candidate for cost-effective, normally-off and ultralow power embedded memory solution for IoT power management.